Research on side information generation algorithm for Wyner-Ziv video coding - SONG Bin; HE Hong; LIU Hai-hua; QIN Hao (Tongxin xuebao)
To reduce the block artifacts and ghosting artifacts of side-information frame in Wyner-Ziv video coding,an overlapped block bi-directional motion compensation algorithm based on the original-image correlation was proposed.Firstly,the correlation of the original image in the encoder is calculated and sent to the decoder.Secondly,the correlation data is used to motion estimation in the decoder to get more accurate motion vector.Then the side information is gener-ated by bi-directional motion compensation.Compared with the existing algorithm,the proposed method can increase the average PSNR（peak signal-to-noise ratio） by 1.5~3dB,and also significantly improve the subjective quality of the side information.